2022
DOI: 10.1039/d1ma00585e
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of SnO2 electron transport layer for efficient planar perovskite solar cells with very low hysteresis

Abstract: In this work, we introduce a bilayer ETL composed of lithium (Li)-doped compact SnO2 (c-SnO2) and potassium-capped SnO2 nanoparticle layers (NP-SnO2) to enhance the electron extraction and charge transport properties in perovskite solar cells, resulting in an improved PCE and a strongly reduced J–V hysteresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 102 publications
1
19
0
Order By: Relevance
“…So we can conclude from this discussion that the voltage scanning rate should be very low (few mV s À1 ), to counter the hysteresis behavior while performing the J-V measurement. [171][172][173]…”
Section: Scan Ratementioning
confidence: 99%
“…So we can conclude from this discussion that the voltage scanning rate should be very low (few mV s À1 ), to counter the hysteresis behavior while performing the J-V measurement. [171][172][173]…”
Section: Scan Ratementioning
confidence: 99%
“…The properties of the films produced were comparable to those produced by other methods. In 2022, Eliwi et al [ 102 ] designed bilayer SnO 2 QDs ETLs. Though different tests, they found that the bilayer ETL composed of lithium-doped compact SnO 2 (c(Li)-SnO 2 ) at the bottom and potassium-capped SnO 2 nanoparticle layers (NP-SnO 2 ) at the top enhanced the charge transport properties of PSCs, and significantly reduced the degree of ion migration.…”
Section: Quantum Dots As Electron Transport Materialsmentioning
confidence: 99%
“…35 Therefore, conventional characterization methods require optimization and suitable new in situ imaging techniques or operando measurement approaches also need to be developed for MHP and PSC research. Typically, capacitance measurements like drive-level capacitance proling (DLCP), 36 space-charge-limited-current (SCLC) 37,38 and deeplevel transient spectroscopy (DLTS), 39 as well as spectrometric characterization methods like steady-state PL emission (ssPL) 40,41 along with in situ techniques are new emerging characterization tools that might be used for an in-depth understanding of PSC materials (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%